Correlation between visual acuity and interface reflectivity measured by pentacam following DSAEK. (26th July 2013) - Heinzelmann, Sonja; Böhringer, Daniel; Maier, Philip C.; Reinhard, Thomas
Abstract. Purpose: Descemet‐stripping automated endothelial keratoplasty (DSAEK) is an advanced method of lamellar endothelial keratoplasty. In comparison with penetrating keratoplasty, visual rehabilitation seems to be faster. Final visual outcome of DSAEK, however, seems to be limited, especially in comparison with Descemet membrane endothelial keratoplasty (DMEK). DSAEK cases without graft failure often do not show any definite correlate for the reduced optical performance. In this study, we tried to correlate visual acuity following DSAEK with interface reflectivity as measured by a rotating Scheimpflug system. Methods: We examined 14 eyes of 13 patients with the pentacam for 2–11 months following DSAEK. Reflectivity of the interface region in the centre of the optical axis as well as central corneal thickness was determined. Statistical correlation between interface reflectivity and best spectacle‐corrected visual acuity, central corneal thickness and follow‐up time was drawn (multifactorial linear regression analysis). Results: Statistically significant correlation between interface reflectivity and BSCVA as well as follow‐up time was found. Reflectivity was highest in regions of interface (metal) particles. There was no statistically significant correlation between interface reflectivity and central corneal thickness. Conclusion: We present a measurable correlate for reduced visual outcome following DSAEK despite a clear graft. Inverse correlation between interface reflectivity and best spectacle‐corrected visual acuity (BSCVA) indicates that irregularities or scarring in the interface region may influence the optical quality following DSAEK.